PASSION AND SELF-EFFICACY BASED DECISION QUALITY: CONCEPTUALIZATION AND EMPIRICAL RESEARCH - Simamora, Bilson (UI Scholars Hub, 2021)
Manuscript type: Research article Research Aims: I the marketing domain, consumer decision quality conceptualization still leaves unfulfilled nodes. When the decisions are made under uncertainty, decision outcomes occurred in the long run, and decision outcomes are determined mostly by customer participation in the value creation process; decision satisfaction as a decision quality sole indicator has less power. Therefore, this study offers passion-and self-efficacy-based decision quality in which passion and self-efficacy acted as a unidimensional construct in its function as a decision quality indicator. Design/methodology/approach: The study used a cross-sectional design. The data were collected with a survey using online questionnaires from 350 conveniently chosen respondents. The data are analyzed using structural equation modeling. Research Findings: Passion and self-efficacy based decision quality is a valid and reliable construct that is also more powerful and has better goodness-of-fit than decision satisfaction in representing decision quality. Its influence on mastery goals is higher than on avoidance goals. Approach motivation goals influence loyalty intention positively and likelihood to switch negatively. Avoidance motivation goals influence loyalty intention negatively and switching likelihood positively. Theoretical Contribution/Originality: Passion and self-efficacy-based decision quality is a concept that is still limited to the present study and can be considered as new to the scientific world. Practitioner/Policy Implication: To increase loyalty intention, a university can fertilize approach achievement and decrease avoidance achievement motivations. Research limitation/Implications: Further research is encouraged to utilize longitudinal design to check a decision and its effect stabilities' in two or more different time points.